Alumni 212" and Ijtima Ulama: A Critical Study Of The Relationship Between Religion And Politics - Rohmawati, Heni (Istawa : Jurnal Pendidikan Islam, 2021)
This article aims to discuss the issue of the relationship between Islam and politics in the â€œAlumni 212â€ and Ijtima Ulama.Â this study was motivated by â€œAction to Defend Islam 212â€.Â Therefor in this first study, the author wants to give about the study of background the formation of â€œAlumni 212â€ and Ijtima Ulama.Â second, critical review about the relationship between Islam and politics of â€œAlumni 212â€ and Ijtima Ulama.Â the purpose of this problem has been to trying flowin is ini and critiquing â€œis there the relationship between Islam and politics of â€œAlumni 212â€ and Ijtima Ulama ?â€.Â Approsch and method in this research use social religion approach is needed and Qualitative method that is the descriptive analysis with library research genre.Â The result from this research indicatesÂ that analysis and critical review about the relationship between Islam and politics of â€œAlumni 212â€ and Ijtima Ulama is that be found relationship from side religion and politics, considering that there are a number of factors that indicateÂ â€œAlumni 212 and Ijtima Ulama contains elements of politics and religion in it.Â The Defending Islam Action I,II AND III has become a new phenomenon in Islam, especially for the conditions of religious life in Indonesia.Â Which then this action becomes the background of the formation of the reunion â€œAlumni 212â€ and Ijtima Ulama, it is feared indicated incarnated as a religious movement mass, and could potentially be a movement on behalf of Islam as a form of identity politics.Â Nevertheless need the existence of functional relationship in the relationship between Islam and state (politics), that is about how Islam can perform its functions in the region or community of the state on the one hand.Â And how the state (politic) can the state can perform its functions as the governing body of the organization of the citizens and its territory is majority Islam on the other hand.